2019
DOI: 10.1002/ps.5521
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Yersinia entomophaga bait for control of larvae of the porina moth (Wiseana spp.), a pest of New Zealand improved grassland systems

Abstract: BACKGROUND Porina is the common name for moths and larvae of the genus Wiseana (Lepidoptera: Hepialidae), some of which are significant pasture pests in New Zealand. Because of environmental concerns and the non‐target effects of insecticide control measures, biological alternatives for the control of insect pests such as porina are required. RESULTS Using a food preference assay and time‐lapse photography, a range of low‐cost food ingredients were assessed for their palatability to porina larvae. Lead candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Wiseana larvae also consumed only a portion of the Y. entomophaga bait presented in bioassays, with an LD 50 of 6 ± 1 × 10 6 CFU per 0.02 g of bait after 7 days. 9 The consistent mortality response, even at low doses in the bioassays, reflects a complex interrelationship between bait consumption by H. arator, growth of Y. entomophaga on the baits before ingestion, 26 and growth of Y. entomophaga after ingestion by H. arator. Although lower doses caused mortality of the target pest, these are not recommended because baits with a low bacterial load of Y. entomophaga (≤1 × 10 3 CFU g −1 ) were prone to contamination with other micro-organisms.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Wiseana larvae also consumed only a portion of the Y. entomophaga bait presented in bioassays, with an LD 50 of 6 ± 1 × 10 6 CFU per 0.02 g of bait after 7 days. 9 The consistent mortality response, even at low doses in the bioassays, reflects a complex interrelationship between bait consumption by H. arator, growth of Y. entomophaga on the baits before ingestion, 26 and growth of Y. entomophaga after ingestion by H. arator. Although lower doses caused mortality of the target pest, these are not recommended because baits with a low bacterial load of Y. entomophaga (≤1 × 10 3 CFU g −1 ) were prone to contamination with other micro-organisms.…”
Section: Discussionmentioning
confidence: 98%
“…numbers when applied to pasture plots. 9 Heteronychus arator is a difficult pest to manage using chemical insecticides. We developed a commercial prototype product capable of controlling H. arator in large-scale field plot experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Coleoptera: Chrysomelidae), 4 porina caterpillars (Wiseana spp. ; Lepidoptera: Hepialidae) 5,6 and P. xylostella. 2,3 These studies have shown that Y. entomophaga persists on apple foliage for up to two days post-spray application 4 and in moist field soil through winter at 3.27 ± 3.27 × 10 3 -3.94 ± 3.12 × 10 4 cells g -1 of soil at 112 days post-field application.…”
Section: Introductionmentioning
confidence: 99%
“…In order to address any safety concerns around the potential long-term persistence or nontarget effects of Y. entomophaga and its Yen-Tc, we used SDS-PAGE analysis and bioassays to assess the stability of the Yen-Tc following foliar application, exposure to UV, or incubation with the intestinal fluids of Yen-Tc-susceptible scarabs (Coleoptera, Scarabaeidae) C. giveni and Adoryphorus couloni (red headed cockchafer), and the nonsusceptible lepidopteran species H. armigera. Through the application of Y. entomophaga to pastures for the control of porina 5,6 or other pastoral pests, the applied bacterium may be ingested by grazing animals. For this reason, the stability profile of the Yen-Tc also was assessed in the rumen fluid of Holstein Friesian cows (Bos taurus) and Romney sheep (Ovis aries).…”
Section: Introductionmentioning
confidence: 99%